Globalisation and growth in Turkiye: Is there a verdict? - Napari, Ayuba; Vergil, Hasan; Kaplan, Muhittin; Khan, Asad Ul Islam (Universitas Islam Indonesia, 2026)
Purpose — Theoretically, the impact of globalisation is ambiguous, and the empirical evidence inconclusive. This study aims to conclusively determine the effects of the various dimensions of globalisation on Turkey’s economic growth.Method — The study employs the autoregressive distributed lag (ARDL) framework to estimate both short-run and long-run effects of globalisation. Globalisation is measured using the KOF Globalisation Index, disaggregated into de jure, de facto, economic, social, and political dimensions. Human capital is proxied by the Human Development Index (HDI), while physical capital is captured by gross fixed capital formation as a percentage of GDP.Findings — The results based on the aggregate globalisation index reveal a positive and significant long-run effect of globalisation on Turkey’s economic growth. However, neither short-run nor long-run effects are observed when aggregate de jure and de facto globalisation indices are used. Furthermore, economic and social globalisation exert a significant negative impact on GDP growth in the short run, though no long-run effects are detected.Implications — The findings suggest that while globalisation can support long-term economic growth, its short-term effects—particularly through economic and social channels—may pose adjustment challenges that require appropriate policy responses.Originality/value — This study contributes to the globalisation–growth literature by providing a comprehensive, disaggregated analysis of globalisation in Turkey using a long time series and the ARDL approach.